Silage Quality of Arrowroot (Maranta arundinacea L.) as Feed for Native Pigs - Roger Y. Ibañez, Jr.; Julius V. Abela; Ginas Aurea A. Villagonzalo; Ulysses A. Cagasan; Manuel D. Gacutan, Jr. (Future Science / FSH-PH Publications, 2026)
High feed costs and limited availability of conventional ingredients constrain native pig production in the Philippines. This study evaluated the silage quality and nutritional composition of arrowroot plant parts ensiled with and without molasses as a potential alternative feed resource. A 2×2 factorial experiment in a completely randomized design was conducted using two plant parts (aerial parts and whole plant) and two additive levels (0 and 4% molasses), with six replicates per treatment. Arrowroot plant biomass was ensiled for 21 days under anaerobic conditions and assessed for yield, fermentation characteristics, physical quality, proximate composition, gross energy (GE), fiber contents, and mineral content. Silage yield, pH (4.87- 4.96), and Fleig scores (69.62-82.82) were not significantly affected (P>0.05) by plant part or molasses supplementation, indicating good to very good silage quality. The addition of Molasses significantly (P<0.05) increased the total soluble solids and improved silage odor. Dry matter content (24.09-28.84%), crude protein (5.62-7.23%), and ether extract (2.37-2.75%) were not significantly (P>0.05) affected by treatments. Gross energy values across all treatments were not statistically differ (P>0.05) from each other, but, molasses-treated silages obtained high GE. Neutral detergent fiber (53.17–55.19%), acid detergent fiber (31.65-34.88%), and hemicellulose (20.31- 21.52%) did not differ significantly (P>0.05) among treatments. A significant plant part and molasses interaction (P<0.05) was observed for phosphorus, whereas potassium, calcium, and magnesium remained unaffected. These results indicated that arrowroot plant silage has favorable fermentation quality and a consistent fibrous energy profile, supporting its potential use in native pig feeding systems.